Robust aspects of solutions in deterministic multiple objective linear programming - Georgiev, Pando Gr; Dinh, The Luc; Pardalos, Panos M. (European journal of operational research, 2013)
We study questions of robustness of linear multiple objective problems in the sense of post-optimal analysis , that is, we study conditions under which a given efficient solution remains efficient when the crite-ria/objective matrix undergoes some alteratio ns. We consider addition or removal of certain criteria, convex combination with another criteria matrix, or small perturbations of its entries. We provide a necessary and sufficient condition for robustness in a verifiable form and give two formulae to compute the radius of robustness.